PENGUKURAN KEBERMANFAATAN ELECTRONIC COMMERCE TERHADAP MINAT BELANJA ONLINE STAF STEBI TANGGAMUS - Dewi, Nirmala; Baza, Irwan (Institut Bakti Nusantara, 2025)
This study aims to measure the influence of Perceived Ease of Use (PEOU), Perceived Usefulness (PU), and Attitude Toward Using (AT) on Behavioural Intention (BI) in the use of the TikTok Shop e-commerce platform among STEBI Tanggamus staff, using the Technology Acceptance Model (TAM) framework. This research employs a quantitative method with Structural Equation Modelling (SEM) to analyse relationships between variables. Data were collected through questionnaires distributed to respondents who actively use TikTok Shop. The results indicate that PEOU has a significant positive effect on PU and AT, PU has a positive effect on AT and BI, and AT has a significant positive effect on BI. These findings suggest that the ease of use and usefulness of TikTok Shop influence user attitudes and online shopping intentions. The study recommends improving the platform’s user interface, promoting benefit-oriented features, and implementing marketing strategies that foster positive user attitudes.